THE EFFECT OF TRANSPARENCY, COMMUNITY PARTICIPATION, AND ACCOUNTABILITY ON MANAGEMENT OF VILLAGE FUNDS IN PONOROGO REGENCY - Khusnatul Zulfa Wafirotin; Umi Septiviastuti (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2019)
This study aims to determine the Effect of Transparency, Community Participation, and Accountability on Village Fund Management (DD) in Ponorogoregency. The research method used is quantitative descriptive with the type of data, namely primary data. Data collection techniques are carried out by distributing questionnaires to respondents. The study was conducted on villages in Pulung and Ngebel Subdistricts, this is because the two sub-districts were not on time in submitting the Realization Report on the Use of DD in the 2017 Budget year to Ponorogoregency DPMD. The population of this study is the Village Chief, Village Secretary, Village Treasurer, Kasi Development, Kasi Community Empowerment, and Chairman of the BPD. The sampling method used was saturated sampling. Based on the population and the sample determination method obtained 156 respondents. Effects of Transparency, Community Participation, and Accountability on DD Management in Ponorogoregency using multiple linear regression analysis and coefficient of determination. Test the quality of the data used is the test of validity and reliability. Furthermore, hypothesis testing using t and F test. The results of this study indicate that the first hypothesis, namely transparency, has a significant positive effect on DD management in Ponorogoregency. The second hypothesis of community participation has a significant positive effect on DD management in Ponorogoregency. The third hypothesis of accountability has a significant positive effect on DD management in Ponorogo.Regency. The fourth hypothesis obtained results that transparency, community participation, and accountability had a significant positive effect on DD management in Ponorogo.This was supported by the results of the recapitulation of respondents' answers and real conditions in the field. Kata kunci :   Transparansi, Partisipasi Masyarakat, Akuntabilitas, Pengelolaan   Dana Desa.